2016
DOI: 10.15625/0866-708x/54/3/7000
|View full text |Cite
|
Sign up to set email alerts
|

Bending and free vibration analysis of functionally graded plates using new eight-unknown shear deformation theory by finite element method

Abstract: In this paper, a new eight-unknown shear deformation theory is developed for bending and free vibration analysis of functionally graded plates by finite element method. The theory based on full twelve-unknown higher order shear deformation theory, simultaneously satisfy zeros transverse stresses at top and bottom surface of FG plates. A four-node rectangular element with sixteen degrees of freedom per node is used. Poisson's ratios, Young's moduli and material densities vary continuously in thickness direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Many works have been performed on the static and dynamic behaviors of FGM structural components in recent years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] To apply the functionally graded (FG) beam structures widely into the engineering practice, an in-depth understanding of their both linear and nonlinear behaviors is essential. In the existing literature, it is found that many researchers have paid their attention to studying on linear behaviors of the FG beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many works have been performed on the static and dynamic behaviors of FGM structural components in recent years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] To apply the functionally graded (FG) beam structures widely into the engineering practice, an in-depth understanding of their both linear and nonlinear behaviors is essential. In the existing literature, it is found that many researchers have paid their attention to studying on linear behaviors of the FG beams.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been performed on the static and dynamic behaviors of FGM structural components in recent years. 114…”
Section: Introductionmentioning
confidence: 99%